Multisystem Inflammatory Syndrome in Infants <12 months of Age, United States, May 2020–January 2021. Issue 7 (July 2021) - Godfred-Cato, Shana; Tsang, Clarisse A.; Giovanni, Jennifer; Abrams, Joseph; Oster, Matthew E.; Lee, Ellen H.; Lash, Maura K.; Le Marchand, Chloe; Liu, Caterina Y.; Newhouse, Caitlin N.; Richardson, Gillian; Murray, Meghan T.; et al.
Abstract : Background: Multisystem inflammatory syndrome in children (MIS-C), temporally associated with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has been identified in infants <12 months old. Clinical characteristics and follow-up data of MIS-C in infants have not been well described. We sought to describe the clinical course, laboratory findings, therapeutics and outcomes among infants diagnosed with MIS-C. Methods: Infants of age <12 months with MIS-C were identified by reports to the CDC's MIS-C national surveillance system. Data were obtained on clinical signs and symptoms, complications, treatment, laboratory and imaging findings, and diagnostic SARS-CoV-2 testing. Jurisdictions that reported 2 or more infants were approached to participate in evaluation of outcomes of MIS-C. Results: Eighty-five infants with MIS-C were identified and 83 (97.6%) tested positive for SARS-CoV-2 infection; median age was 7.7 months. Rash (62.4%), diarrhea (55.3%) and vomiting (55.3%) were the most common signs and symptoms reported. Other clinical findings included hypotension (21.2%), pneumonia (21.2%) and coronary artery dilatation or aneurysm (13.9%). Laboratory abnormalities included elevated C-reactive protein, ferritin, d-dimer and fibrinogen. Twenty-three infants had follow-up data; 3 of the 14 patients who received a follow-up echocardiogram had cardiac abnormalities during or after hospitalization. Nine infants had elevated inflammatory markers up to 98 days postdischarge. One infant (1.2%) died after experiencing multisystem organ failure secondary to MIS-C. Conclusions: Infants appear to have a milder course of MIS-C than older children with resolution of their illness after hospital discharge. The full clinical picture of MIS-C across the pediatric age spectrum is evolving.